Pengaruh Persepsi Pelanggan Terkait Etika Bisnis Islam Terhadap Kepuasan Pelanggan Pengguna E-Commerce. - Sholihah, Farah Aunti; Indrarini, Rachma (Universitas Negeri Surabaya, 2019)
Low e-commerce consumer protection resulted in a lack of customer satisfaction. In increasing customer satisfaction is necessary the existence of Islamic business ethics applicability by traders.This research aims to test the influence of customer perception related application of Islamic business ethics based on the nature of the noble Prophet Muhammad towards customer satisfaction is measured using a likert scale and analyzed using spss version 23 fore-commerce users. This analysis technique is used in a simple linear regression analysis to apply and test T. The results showed that customer perception of the Islamic business ethics related to customer statisfaction of users of E-commerce.